An analysis of complications in secondary bone grafting in patients with unilateral complete cleft lip and palate. Issue 2 (3rd March 2016) - Wiedel, Anna-Paulina; Svensson, Henry; Schönmeyr, Björn; Becker, Magnus
Abstract: Aim : The aim of this investigation was to assess the outcome of secondary alveolar bone grafts 6 months after the procedure and examine the possible influence of patient sex, age at surgery, cleft width, and dehiscence of mucosa and sequestered bone at 2 weeks. Methods : Thirty-nine consecutive patients with unilateral complete cleft lip and palate were reconstructed with secondary alveolar bone grafting. Age at surgery ranged from 7.3–12.5 years (mean = 8.6). Cleft width varied between 2.2–14 mm (mean = 7.3). Bone was harvested either from the iliac crest or from the chin. Two-dimensional dental radiographs of the cleft area were taken before and 6 months after surgery. Results : Two weeks after surgery, 10 patients had minor dehiscence of the sutured gingival tissues and five had bone sequesters. However, only one of the treatments turned out to be unsuccessful with a Bergland index of IV. Twenty-nine patients had an initial uneventful course; but, at a follow-up 6 months later, two patients had a Bergland index of III and four a Bergland index of IV. In three of these cases, there were circumstances that could have contributed to the lack of success; but, in the remaining three, no such circumstances could be identified. Conclusion : The success rate of secondary bone grafting is high, and initial wound healing problems do not necessarily lead to a failed reconstruction. Failure may be related to factors such as exposed tooth enamel during an operation, postoperative infection, and poor compliance. Still, failed operations occur without any obvious causes.